(untitled) (Research, Society and Development, 2022)
This study aimed at the assessment and monitoring of digital image quality parameters resulting from the use of portable X-ray equipment in clinical examinations. A multicentric study was conducted for quality assessment of images produced using the portable NOMAD® with the DIGORA® ™ Optime UV computed radiography (CR) system. The digital image quality was evaluated in terms of high- and low-contrast spatial resolution, contrast noise ratio (CNR), and signal-to-noise ratio (SNR). The samples comprised six biomaterials: zirconia (Zr), lyophilized bone (LB), photopolymerizable restorative resin (PRR), glass ionomer cement (GIC), GIC photopolymerizable (GICP), and double adhesive resin cement (DARC). The DICOM image (processed pixels) and raw data (without processing) were quantitatively analyzed. The qualitative visual analysis was performed in an adequately illuminated environment and then repeated in an environment equivalent to that of a clinical practice using conventional monitoring equipment. The relative biomaterial contrast was normalized by the high-contrast result of Zr. The Zr image demonstrated no noise because the standard deviation of the digital image biomaterial pixel mean was zero. In contrast, the relative SNR of the biomaterials was normalized by the DARC result. The relative CNR values according to different aluminum thicknesses were 0.11 for LB and 0.3–0.35 for PRR, GIC, and GICP. The spatial resolution was identical for both high-resolution and conventional monitors; however, for a 0.2-s clinical exposure, the resolution produced by the high-quality monitor increased. The quality control tests indicated the compatibility of the CR system-assisted portable X-ray equipment, verifying the status and image quality.